(untitled) (Journal of Bangladesh Academy of Sciences, 2024)
The study was conducted to observe the physical and chemical properties of the soils of the Payra thermal power plant’s surrounding areas. The textural class of 55 collected soil samples was mostly Silt loam, with few Silty clay loam soils. Soil pH ranges from 3.72 to 7.82, with more than 80 % being acidic and only 4% slightly alkaline. The 23 % of samples were highly acidic (pH<4.5). The electrical conductivity ranged from 0.91 to 23.95 dS/m, with 47% of the samples having EC values greater than 8 dS/m; those sample sites were unsuitable for crop cultivation. There was a significant difference between Olsen P and Bray P in soil, having 0.73 to 13.87 and 9.29 to 42.60 ppm, respectively. All the samples had very high sulfur contents (34.3 to 601.4 ppm). Most soil samples (78%) contained very high sodium content. J. Bangladesh Acad. Sci. 48(2); 273-276: December 2024